Low-Dose Fluoxetine in Four Children with Autistic Spectrum Disorder Improves Self-Injurious Behavior, ADHD-Like Symptoms, and Irritability - Juan Pablo Lucchelli; Gilles Bertschy (Case Reports in Psychiatry)
Autism Spectrum Disorder (ASD) is defined by the copresence of two core symptoms: alteration in social communication and repetitive behaviors and/or restricted interests. In ASD children and adults, irritability, self-injurious behavior (SIB), and Attention Deficit and Hyperactivity Disorders- (ADHD-) like symptoms are regularly observed. In these situations, pharmacological treatments are sometimes used. Selective Serotonin Reuptake Inhibitors- (SSRI-) based treatments have been the subject of several publications: case reports and controlled studies, both of which demonstrate efficacy on the symptoms mentioned above, even if no consensus has been reached concerning their usage. In this article four clinical cases of children diagnosed with ASD and who also present ADHD-like symptoms and/or SIB and/or other heteroaggressive behaviors or irritability and impulsivity treated with low doses of fluoxetine are presented.